Regulation of proline and glucose transport in mouse intestine by dietary substrate levels. - Karasov, W H (1983)
Active uptake of D-glucose and L-proline at 50 mM was measured in everted intestinal sleeves of mice whose dietary carbohydrate and protein levels were being varied experimentally. Compared to a nearly carbohydrate-free meat diet, a 50% carbohydrate laboratory chow diet stimulated active glucose uptake in the proximal intestine without affecting proline uptake, passive glucose permeability, or several measures of mucosal mass. Switching from a low-protein high-carbohydrate to a high-protein no-carbohydrate diet reversibly stimulated proline uptake while inhibiting glucose uptake. For each solute and diet switch, the stimulation of transport was complete within 1 day, while the inhibition required several days. The results imply induction and repression of intestinal glucose and proline transport by dietary substrate levels. This mechanism, in conjunction with the normal gradient of nutrient concentrations along the intestine, is probably largely responsible for the gradient in nutrient transport along the intestine.